(untitled) (Global Journal of Management and Business Research, 2025)
Abstract- This study investigates the impact of Corporate Social responsibility on Brand Satisfaction among hotel sectors in General Santos City Environmental and Ethical Responsibility were used as indicators for CSR while brand image and brand equity were used as indicators for Brand Satisfaction The study targeted 385 respondents who were guests of the hotels in General Santos City Data were collected from August 2024 to November 2024 through face-to-face surveys The researcher also employed an online survey through QR code scanning for some hotels that are practicing environmental sustainability This study was correlational employing different statistical treatments to address the study s objectives Frequency counts and percentages were used to analyze the respondents demographic data weighted mean and standard deviation were used to analyze the CSR and brand satisfaction level